Nickel‐Catalyzed Enantioselective Conjunctive Cross‐Coupling of 9‐BBN Borates. (17th August 2017) - Chierchia, Matteo; Law, Chunyin; Morken, James P.
Abstract: Catalytic enantioselective conjunctive cross‐coupling between 9‐BBN borate complexes and aryl electrophiles can be accomplished with Ni salts in the presence of a chiral diamine ligand. The reactions furnish chiral 9‐BBN derivatives in an enantioselective fashion and these are converted to chiral alcohols and amines, or engaged in other stereospecific C−C bond forming reactions.